Intelligent concrete pole and preparation method thereof
By using steel slag micropowder, silicon carbide and acid to treat single-wall carbon nanotubes in concrete poles to form a conductive network, the resistivity of the poles is monitored in real time, and the problem of inability to monitor the actual stress and aging of the poles in the prior art is solved, and accurate monitoring and fault warning of the poles' operating status is achieved, which reduces safety hazards.
Patent Information
- Application Number
- CN202411575726.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-06
- Publication Date
- 2025-02-28
AI Technical Summary
The existing pole monitoring methods can only monitor the inclination angle of the pole body, and cannot monitor the actual stress and aging of the pole body, which makes it difficult to detect faults or accidents in a timely manner, posing safety hazards.
Single-wall carbon nanotube composites are used to process steel slag micropowder, silicon carbide and acid to form a continuous conductive network in the concrete. By real-time monitoring of the resistivity between the first electrode patch and the second electrode patch, the operation of the pole is accurately controlled.
It realizes accurate monitoring of the stress and operating status of the pole, detects potential faults in advance, reduces safety hazards, and improves the safety and reliability of power grid operation.
Smart Images

Figure CN119531657A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of cement pole products, and in particular to an intelligent concrete pole and a preparation method thereof. Background Art
[0002] Electric poles play the role of supporting overhead wires. my country has a history of more than 100 years in the development of electric pole manufacturing. Common electric poles include wooden poles, concrete poles, power towers, etc. Electric poles can be seen everywhere, whether in mountains and gullies or in urban plains.
[0003] As the service life of the poles increases or as the geological conditions change, the poles will tilt. Currently in the power transmission and distribution network system, the monitoring of the operating status of the poles is usually carried out by hanging a controller with a gyroscope on the pole to calibrate the verticality of the pole. If the pole is offset or tilted, the gyroscope will report the parameters of the X, Y, and Z axes to the monitoring platform. The platform will conduct a comprehensive assessment of the operating status of the power facilities, thereby determining whether there is a fault or accident in the operation of the pole at that time.
[0004] This traditional monitoring method can only monitor the inclination angle of the pole, but cannot monitor the actual stress mode of the pole and the aging degree of the pole body, such as cracking, bending, bumping and other parameters. Therefore, it is difficult to effectively inspect and manage the poles, and there is a certain lag. For example, at present, when the staff usually learn of an abnormal situation, a fault or accident has actually occurred, and then they perform maintenance or inspection on the pole. However, they are unable to detect abnormal stress conditions and operating conditions of the pole before the accident occurs, and perform maintenance and inspection in time, thus burying a safety hazard in the operation of the power grid. Summary of the invention
[0005] In order to solve the deficiencies in the prior art, the present application provides an intelligent concrete pole and a preparation method thereof. In the present application, a continuous conductive network is formed in the concrete by compounding steel slag powder, silicon carbide and acid-treated single-walled carbon nanotubes. By real-time monitoring of the resistivity between the first electrode patch and the second electrode patch, the operation of the pole can be accurately controlled, so that the staff can maintain and repair the pole in time, reducing the safety hazards in the operation of the transmission and distribution lines.
[0006] In the first aspect, the present application provides a smart concrete pole, which adopts the following technical solution: A smart concrete pole, comprising a pole body and a current collection device arranged on the pole body, wherein the pole body is cast by smart concrete, and the smart concrete comprises the following components by weight percentage: 250-290 parts of cement, 900-1100 parts of crushed stone, 380-500 parts of sand, 100-160 parts of steel slag powder, 35-45 parts of silica fume, 30-45 parts of nano silicon carbide, 1-3 parts of acid-treated single-walled carbon nanotubes, 5-10 parts of dispersant and 160-180 parts of water; The acid-treated single-walled carbon nanotubes are single-walled carbon nanotubes treated with concentrated sulfuric acid, concentrated nitric acid and citric acid.
[0007] The single-walled carbon nanotubes used in the present application have a diameter of 0.6-2 nm and a length of 5-30 μm.
[0008] By adopting the above technical solution, acid-treated single-walled carbon nanotubes have good conductivity and can easily form a conductive network in concrete to provide a channel for electron transmission; steel slag powder and nano-silicon carbide also have certain conductivity and good dispersion, and can be filled between single-walled carbon nanotubes to help form a continuous conductive network, which can improve the sensitivity and accuracy of monitoring the stress of concrete poles. In addition, steel slag powder and nano-silicon carbide can also effectively improve the mechanical properties, impermeability and frost resistance of concrete, and improve the overall performance of concrete.
[0009] Due to the strong van der Waals forces between single-walled carbon nanotubes, they are easily entangled and agglomerated. After being treated with concentrated sulfuric acid, concentrated nitric acid and citric acid, active groups such as carboxyl and hydroxyl groups are introduced on their end groups or side walls, changing the surface charge distribution of the single-walled carbon nanotubes, thereby improving the dispersion of the single-walled carbon nanotubes in concrete. Dispersants are added to the concrete to further promote the dispersion of single-walled carbon nanotubes in the concrete, improving the conductivity of the concrete, so that the staff can understand the operating status of the poles through the current collection device, maintain and repair the lines in advance, and prevent the occurrence of safety accidents.
[0010] Preferably, the current collection device comprises a first electrode patch and a second electrode patch, the first electrode patch is arranged above the second electrode patch, and the distance between the first electrode patch and the second electrode patch is 30-50 cm.
[0011] By adopting the above technical solution, the resistivity between the first electrode patch and the second electrode patch is monitored in real time. The power grid system can output digital signals according to the dynamic changes of the resistivity, intuitively observe the stress conditions of the poles, improve the monitoring system of the power grid, more comprehensively monitor the line safety, and reduce the potential safety hazards in the operation of the transmission and distribution lines.
[0012] Preferably, the particle size of the steel slag powder is 10-20 μm.
[0013] By adopting the above technical solution, steel slag powder with a particle size of 10-20 μm is used to fill the tiny gaps in the concrete, which can effectively improve the mechanical properties and frost resistance of the concrete.
[0014] Preferably, the mass ratio of the steel slag powder, nano-silicon carbide and acid-treated single-walled carbon nanotubes is (60-80):(15-25):1.
[0015] By adopting the above technical solution and adjusting the mass ratio of steel slag powder, nano-silicon carbide and acid-treated single-walled carbon nanotubes, it is helpful to form a continuous conductive network in the concrete, thereby more accurately monitoring the stress condition and operating status of the poles, making it easier for staff to carry out maintenance and repairs in a timely manner.
[0016] In some preferred embodiments, the mass ratio of the steel slag powder, nano-silicon carbide and acid-treated single-walled carbon nanotubes can be 70:20:1, 80:25:1 or 60:15:1, etc.
[0017] Preferably, the dispersant includes sodium carboxymethyl cellulose, polyvinyl pyrrolidone and sodium alginate.
[0018] By adopting the above technical scheme, the carboxyl group of sodium carboxymethyl cellulose can be partially ionized in water, so that the molecule has a negative charge, which attracts the charge on the surface of the acid-treated single-walled carbon nanotubes and adsorbs on the surface of the acid-treated single-walled carbon nanotubes. At the same time, sodium carboxymethyl cellulose is also a polymer compound, and its polymer chain will surround the acid-treated single-walled carbon nanotubes to prevent them from agglomerating. Polyvinyl pyrrolidone is a polymer, and its molecular chain can surround the acid-treated single-walled carbon nanotubes, further consolidating the adsorption effect of sodium carboxymethyl cellulose, increasing the steric hindrance between the acid-treated single-walled carbon nanotubes, and preventing them from entanglement. Sodium alginate molecules contain multiple hydrophilic groups, which can form a hydration network with water molecules and enhance the stability of carbon nanotubes in solution. The combination of the three can further promote the stable dispersion of acid-treated single-walled carbon nanotubes in concrete, thereby improving the conductivity of concrete.
[0019] Preferably, the mass ratio of sodium carboxymethyl cellulose, polyvinyl pyrrolidone and sodium alginate is (2-5): (1-3): 1.
[0020] By adopting the above technical solution and further adjusting the mass ratio of sodium carboxymethyl cellulose, polyvinyl pyrrolidone and sodium alginate, it is helpful to improve the dispersion of acid-treated single-walled carbon nanotubes in concrete, thereby improving the conductive properties of concrete.
[0021] In some preferred embodiments, the mass ratio of sodium carboxymethyl cellulose, polyvinyl pyrrolidone and sodium alginate can be 2:3:1, 4:2:1 or 5:1:1, etc.
[0022] Preferably, the method for preparing the acid-treated single-walled carbon nanotubes is as follows: A1. Evenly mix concentrated sulfuric acid, concentrated nitric acid and citric acid aqueous solution to prepare a mixed acid solution; A2, placing the single-walled carbon nanotubes into the mixed acid solution and performing ultrasonic treatment to obtain a mixed solution; A3. Separating the mixed solution into solid and liquid, and washing and drying the separated single-walled carbon nanotube precipitate to obtain the acid-treated single-walled carbon nanotube.
[0023] Furthermore, in step A2, the ultrasonic treatment conditions are as follows: ultrasonic frequency: 20kHz-30kHz, ultrasonic temperature: 50°C-70°C, ultrasonic time: 5-9h.
[0024] By adopting the above technical solution, the mixed acid solution will oxidize the single-walled carbon nanotubes, generating hydrophilic groups on their surface, and the surface of the single-walled carbon nanotubes will change from hydrophobic to hydrophilic, so that they can be dispersed in water, thereby improving the dispersibility of the single-walled carbon nanotubes.
[0025] Preferably, the concentration of the concentrated sulfuric acid is 90%-98%, the concentration of the concentrated nitric acid is 60%-70%, the concentration of the citric acid aqueous solution is 5%-15%, and the volume ratio of the concentrated sulfuric acid, concentrated nitric acid and citric acid aqueous solution is (2-4):1:(7-9).
[0026] By adopting the above technical scheme, using concentrated sulfuric acid, concentrated nitric acid and citric acid aqueous solutions of the above concentrations, and controlling the volume ratio of the three within the above range, the mixed acid solution has a better treatment effect on single-walled carbon nanotubes, and can improve the dispersibility of single-walled carbon nanotubes while minimizing the interruption of single-walled carbon nanotubes, so that they still have good conductive properties.
[0027] In some specific embodiments, the concentration of the concentrated sulfuric acid is 95%, the concentration of the concentrated nitric acid is 68%, and the concentration of the citric acid aqueous solution is 10%, all of which are easily available.
[0028] In some preferred embodiments, the volume ratio of concentrated sulfuric acid, concentrated nitric acid and citric acid aqueous solution can be 3:1:8, 2:1:9, or 4:1:7, etc.
[0029] Preferably, in step A2, 50-70 mL of mixed acid solution is used for treating 1 g of single-walled carbon nanotubes.
[0030] By adopting the above technical solution, part of the single-walled carbon nanotubes can be fully treated with acid, and the other part of the single-walled carbon nanotubes can still maintain a large aspect ratio, thereby avoiding a significant decrease in the conductivity of the single-walled carbon nanotubes after being treated with acid.
[0031] In a second aspect, the present application provides a method for preparing a smart concrete pole, which adopts the following technical solution: A method for preparing an intelligent concrete pole comprises the following steps: S1, mixing cement, crushed stone, sand, steel slag powder, silica fume, nano silicon carbide, a dispersant and water uniformly to obtain a premix; S2, adding the acid-treated single-walled carbon nanotubes into the premix and mixing evenly to obtain concrete; S3, pre-embedding the first electrode patch and the second electrode patch in a mold, then pouring the concrete into the mold, and demoulding after the concrete is formed to obtain a smart concrete pole.
[0032] By adopting the above technical solution, the dispersant is first mixed with other raw materials except the acid-treated single-walled carbon nanotubes, and then the acid-treated single-walled carbon nanotubes are added, so that the acid-treated single-walled carbon nanotubes can fully contact with the dispersant and stably dispersed in the concrete. In addition, the preparation of concrete poles according to the above method is simple to operate and convenient for factory production.
[0033] In summary, the present application includes at least one of the following beneficial technical effects: 1. In this application, a continuous conductive network is formed in the concrete by compounding steel slag powder, silicon carbide and acid-treated single-walled carbon nanotubes. By real-time monitoring of the resistivity between the first electrode patch and the second electrode patch, the operation of the pole can be accurately controlled; 2. The present application uses a mixed acid solution of concentrated sulfuric acid, concentrated nitric acid and citric acid aqueous solution to acid-treat single-walled carbon nanotubes, so that the surface of the single-walled carbon nanotubes changes from hydrophobic to hydrophilic, improves its dispersibility, and makes it better dispersed in concrete, thereby improving the electrical conductivity of the concrete; 3. In the present application, a dispersant consisting of sodium carboxymethyl cellulose, polyvinyl pyrrolidone and sodium alginate is added to the concrete. The three agents synergistically improve the dispersibility of the acid-treated single-walled carbon nanotubes from different directions, so that the single-walled carbon nanotubes can be stably dispersed in the concrete. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 This is a schematic diagram of the structure of the smart concrete pole in Example 1 of the present application.
[0035] In the figure, 1, rod body, 2, current collection device; 21, first electrode patch; 22, second electrode patch. DETAILED DESCRIPTION
[0036] In order to make the present application easier to understand, the present application will be further described in detail below in conjunction with the examples, which are merely illustrative and are not intended to limit the scope of application of the present application. The raw materials or components used in the present application can be obtained through commercial routes or conventional methods unless otherwise specified.
[0037] Source of raw materials: Cement was P·O42.5 ordinary Portland cement purchased from Henan Hao Nai Building Materials Co., Ltd.; Steel slag powder, particle size is 10-20μm; Silica fume, particle size 1250 mesh, density 2.85g / cm 3 , purity is 90%; Sodium carboxymethyl cellulose, CAS number 9004-32-4, active ingredient content 99%, density 1.6g / cm 3 ; Polyvinyl pyrrolidone, CAS number 9003-39-8, active ingredient content 99%, density 1.69g / cm 3 , purchased from Huzhou Shenhua Polymer Materials Co., Ltd.; Sodium alginate, CAS No. 9001-73-4, active ingredient content 99%, was purchased from Anhui Zhonghong Bioengineering Co., Ltd.
[0038] Preparation Example 1: Preparation of acid-treated single-walled carbon nanotubes The preparation method of acid-treated single-walled carbon nanotubes in Preparation Example 1 is as follows: 15L of 95% concentrated sulfuric acid, 5L of 68% concentrated nitric acid and 40L of 10% citric acid aqueous solution are mixed evenly to obtain a mixed acid solution, and then 1kg of single-walled carbon nanotubes are immersed in 60L of the mixed acid solution, and the mixed solution is placed in an ultrasonic processor for ultrasonic treatment at an ultrasonic frequency of 25kHz and ultrasonicated at 60°C for 7h to obtain a mixed solution. The mixed solution is separated into solid and liquid using a suction filter, and the separated single-walled carbon nanotube precipitate is repeatedly washed with deionized water until the pH of the deionized water is 6.5, and then the single-walled carbon nanotubes are placed at 60°C and dried for 6h to obtain acid-treated single-walled carbon nanotubes. The volume ratio of concentrated sulfuric acid, concentrated nitric acid and citric acid aqueous solution is 3:1:8.
[0039] Preparation Example 2: Preparation of acid-treated single-walled carbon nanotubes The difference between Preparation Example 2 and Preparation Example 1 is that the amounts of concentrated sulfuric acid, concentrated nitric acid and citric acid aqueous solution in the mixed acid solution are different. In Preparation Example 2, the mixed acid solution is prepared by uniformly mixing 10L of 95% concentrated sulfuric acid, 5L of 68% concentrated nitric acid and 45L of 10% citric acid aqueous solution, that is, the volume ratio of concentrated sulfuric acid, concentrated nitric acid and citric acid aqueous solution is 2:1:9.
[0040] Preparation Example 3: Preparation of acid-treated single-walled carbon nanotubes The difference between Preparation Example 3 and Preparation Example 1 is that the amounts of concentrated sulfuric acid, concentrated nitric acid and citric acid aqueous solution in the mixed acid solution are different. In Preparation Example 3, the mixed acid solution is prepared by uniformly mixing 20L of 95% concentrated sulfuric acid, 5L of 68% concentrated nitric acid and 35L of 10% citric acid aqueous solution, that is, the volume ratio of concentrated sulfuric acid, concentrated nitric acid and citric acid aqueous solution is 4:1:7.
[0041] Preparation Example 4: Preparation of acid-treated single-walled carbon nanotubes The difference between Preparation Example 4 and Preparation Example 1 is that 1 kg of single-walled carbon nanotubes is immersed in 40 L of mixed acid solution for treatment, and the rest is the same as Preparation Example 1.
[0042] Preparation Example 5: Preparation of acid-treated single-walled carbon nanotubes The difference between Preparation Example 5 and Preparation Example 1 is that 1 kg of single-walled carbon nanotubes is immersed in 80 L of mixed acid solution for treatment, and the rest is the same as Preparation Example 1.
[0043] Example 1: Preparation of smart concrete poles Reference Figure 1 In Examples 1-3, the intelligent concrete pole includes a pole body 1 and a current collection device 2. The pole body 1 is cast by intelligent concrete and fixedly installed on the ground in the vertical direction. The pole body 1 can be a cylinder or a square. The current collection device 2 includes a first electrode patch 21 and a second electrode patch 22. The first electrode patch 21 and the second electrode patch 22 are both pre-buried in the side wall of the pole body 1 along the circumferential direction of the axis of the pole body 1. The first electrode patch 21 is located 40 cm above the second electrode patch 22 to ensure the accuracy of the sampling data. The width of the first electrode patch 21 and the second electrode patch 22 is 8 cm. Both are made of copper. It should be noted that the part of the pole body 1 located below the second electrode patch 22 is buried below the ground.
[0044] The raw materials and dosages of the smart concrete in Examples 1-3 are shown in Table 1, wherein the acid-treated single-walled carbon nanotubes are the acid-treated single-walled carbon nanotubes prepared in Preparation Example 1.
[0045] The preparation method of the smart concrete pole in Examples 1-3 is as follows: first, cement, gravel, sand, steel slag powder, silica fume, nano-silicon carbide, a dispersant and water are mixed evenly to obtain a premix; then, acid-treated single-walled carbon nanotubes are added to the premix and mixed evenly again to obtain smart concrete; the first electrode patch and the second electrode patch are pre-embedded in a mold, and then concrete is poured into the mold, and the mold is demolded after the concrete is formed to obtain a smart concrete pole.
[0046] Table 1. Raw materials and dosage of smart concrete in Examples 1-7 (kg)
[0047] Embodiment 4-5: The raw materials and dosages of the smart concrete in Example 4-5 are shown in Table 1. The difference between Example 4-5 and Example 1 is that the dosages of steel slag powder, nano silicon carbide and acid-treated single-walled carbon nanotubes are different, and the rest are the same as Example 1.
[0048] Embodiment 6-7: The raw materials and dosages of the smart concrete in Examples 6-7 are shown in Table 1. The difference between Examples 6-7 and Example 1 is that the dosages of sodium carboxymethyl cellulose, polyvinyl pyrrolidone and sodium alginate in the dispersant are different, and the rest are the same as Example 1.
[0049] Embodiment 8-11: The difference between Examples 8-11 and Example 1 is that the acid-treated single-walled carbon nanotubes are the acid-treated single-walled carbon nanotubes prepared in Preparation Examples 2-5, respectively, and the rest is the same as Example 1.
[0050] Comparative Example 1: The difference between Comparative Example 1 and Example 1 is that untreated single-walled carbon nanotubes are used in equal amounts to replace the acid-treated single-walled carbon nanotubes, and the rest is the same as Example 1.
[0051] Comparative Example 2: The difference between Comparative Example 2 and Example 1 is that the dispersant is sodium carboxymethyl cellulose, and the rest is the same as Example 1.
[0052] Comparative Example 3: The difference between Comparative Example 3 and Example 1 is that the dispersant is polyvinyl pyrrolidone, and the rest is the same as Example 1.
[0053] Comparative Example 4: The difference between Comparative Example 4 and Example 1 is that the dispersant is sodium alginate, and the rest is the same as Example 1.
[0054] Performance testing: After demoulding, the smart concrete poles prepared in Examples 1-11 and Comparative Examples 1-4 were cured for 28 days at a temperature of 20°C and a humidity of 95%, and then their performance was tested, including compressive strength and resistivity. The compressive strength was tested with reference to GB / T 17671-1999 "Test Method for Strength of Cement Mortar (ISO Method)", and the resistivity was tested with reference to the voltammetric method. The specific test results are shown in Table 2.
[0055] Table 2
[0056] It can be seen from the test data in Table 2 that the smart concrete poles prepared in Examples 1-11 and Comparative Examples 1-4 have good compressive strength and can meet actual use requirements. The conductive performance of the smart concrete poles prepared in Examples 1-11 is significantly better than that of the smart concrete poles prepared in Comparative Examples 1-4.
[0057] From the test data of Examples 1-5, it can be seen that the preparation raw materials and their dosage of the smart concrete in Example 1 are more appropriate when preparing the poles. The compressive strength of the poles in Example 1 can reach 68.9MPa, the resistivity is low, and the conductivity is good. After adjusting the dosage of steel slag powder, nano silicon carbide and acid-treated single-walled carbon nanotubes, it was found that the overall performance of the poles was better when the mass ratio of the three was 67.5:20:1.
[0058] It can be seen from the test data of Examples 1, 6-7 and Comparative Examples 2-4 that, compared with the use of a single type of dispersant, the dispersant prepared by compounding sodium carboxymethyl cellulose, polyvinyl pyrrolidone and sodium alginate has a better dispersion effect on the acid-treated single-walled carbon nanotubes, especially when the mass ratio of sodium carboxymethyl cellulose, polyvinyl pyrrolidone and sodium alginate is (2-5): (1-3): 1, the acid-treated single-walled carbon nanotubes can be evenly dispersed in the concrete, which helps to improve the conductive performance of the smart concrete poles.
[0059] From the test data of Examples 8-11 and Comparative Example 1, it can be seen that the acid treatment of single-walled carbon nanotubes helps to improve the conductivity of the smart concrete poles, which may be due to the improved dispersibility of the single-walled carbon nanotubes after the acid treatment. When the single-walled carbon nanotubes are subjected to acid treatment, it is more appropriate to immerse 1 kg of single-walled carbon nanotubes in 60 L of mixed acid solution. Too much or too little use of the mixed acid solution will affect the dispersibility and conductivity of the single-walled carbon nanotubes, thereby affecting the overall performance of the smart concrete poles.
[0060] It should be noted that the embodiments described above are only used to explain the present application and do not constitute any limitation to the present application. The present application is described with reference to typical embodiments, but it should be understood that the words used therein are descriptive and explanatory words, rather than restrictive words. The present application may be modified as specified within the scope of the claims of the present application, and the present invention may be revised without departing from the scope and spirit of the present application. Although the present application described therein relates to specific methods, materials and embodiments, it does not mean that the present application is limited to the specific examples disclosed therein. On the contrary, the present application can be extended to all other methods and applications with the same functions.
Claims
1. An intelligent concrete pole, characterized in that: The electric pole comprises a pole body (1) and a current collection device (2) arranged on the pole body (1); the pole body (1) is cast by intelligent concrete, and the intelligent concrete comprises the following components by weight: 250-290 parts of cement, 900-1100 parts of crushed stone, 380-500 parts of sand, 100-160 parts of steel slag powder, 35-45 parts of silica fume, 30-45 parts of nano silicon carbide, 1-3 parts of acid-treated single-walled carbon nanotubes, 5-10 parts of dispersant and 160-180 parts of water; The acid-treated single-walled carbon nanotubes are single-walled carbon nanotubes treated with concentrated sulfuric acid, concentrated nitric acid and citric acid.
2. The intelligent concrete pole according to claim 1, characterized in that: The current collection device (2) comprises a first electrode patch (21) and a second electrode patch (22), wherein the first electrode patch (21) is arranged above the second electrode patch (22), and the distance between the first electrode patch (21) and the second electrode patch (22) is 30-50 cm.
3. The intelligent concrete pole according to claim 1, characterized in that: The particle size of the steel slag powder is 10-20 μm.
4. The intelligent concrete pole according to claim 1, characterized in that: The mass ratio of the steel slag powder, nano silicon carbide and acid-treated single-walled carbon nanotubes is (60-80):(15-25):
1.
5. The intelligent concrete pole according to claim 1, characterized in that: The dispersant includes sodium carboxymethyl cellulose, polyvinyl pyrrolidone and sodium alginate.
6. The intelligent concrete pole according to claim 5, characterized in that: The mass ratio of sodium carboxymethyl cellulose, polyvinyl pyrrolidone and sodium alginate is (2-5): (1-3):
1.
7. The intelligent concrete pole according to claim 1, characterized in that: The preparation method of the acid-treated single-walled carbon nanotubes is as follows: A1. Evenly mix concentrated sulfuric acid, concentrated nitric acid and citric acid aqueous solution to prepare a mixed acid solution; A2, placing the single-walled carbon nanotubes into the mixed acid solution and performing ultrasonic treatment to obtain a mixed solution; A3. Separating the mixed solution into solid and liquid, and washing and drying the separated single-walled carbon nanotube precipitate to obtain the acid-treated single-walled carbon nanotube.
8. The intelligent concrete pole according to claim 7, characterized in that: The concentration of the concentrated sulfuric acid is 90%-98%, the concentration of the concentrated nitric acid is 60%-70%, the concentration of the citric acid aqueous solution is 5%-15%, and the volume ratio of the concentrated sulfuric acid, the concentrated nitric acid and the citric acid aqueous solution is (2-4):1:(7-9).
9. The intelligent concrete pole according to claim 7, characterized in that: In the step A2, 50-70 mL of the mixed acid solution is used to treat 1 g of the single-walled carbon nanotubes.
10. A method for preparing an intelligent concrete pole according to any one of claims 1 to 8, characterized in that: The preparation method comprises the following steps: S1. Mix cement, crushed stone, sand, steel slag powder, silica fume, nano silicon carbide, dispersant and water to obtain a premix; S2, adding the acid-treated single-walled carbon nanotubes into the premix and mixing evenly to prepare smart concrete; S3, pre-embedding the first electrode patch and the second electrode patch in a mold, then pouring the concrete into the mold, and demoulding after the concrete is formed to obtain a smart concrete pole.